HOW TO DEVELOP THE COMPETENCE OF INTERCULTURAL COMMUNICATION OF NONENGLISH MAJOR INDONESIAN STUDENTS - Idris, Mas Muhammad (Proceeding of International Conference on Islamic Education (ICIED); Vol 2 No 1 (2017): Proceeding of International Conference on Islamic Education (ICIED), 2017)
In fact, most of the Indonesian students especially for them who are not from English major are occasionally lack the ability to use the English language properly in the context of intercultural communication. It happens due to their minimum understandings of English language as a tool of communication. Thus, some miscommunication will frequently happen. Therefore, the purposes of this paper are to provide the fundamental concepts of intercultural competence that focus on foreign language teaching and learning; and investigate the students' intercultural communication competence. Moreover, the writer proposes some principles concerning the factors of how intercultural communication competence influences the students' ability to understand the cultural meanings of language, especially for the English language. Literature-based paper will be utilized by the writer as a method, the results are: intercultural knowledge, attitude, and skill are highlighted as the foundation for non-English major Indonesian students to be interculturally competent, the five core principles that underlie the intercultural perspectives of language teaching and learning; and two other factors related to the intercultural communication competence which will be discussed in this paper.